Platelet dysfunction caused by a novel thromboxane A2 receptor mutation and congenital thrombocytopenia in a case of mild bleeding. (17th February 2020) - Bugert, Peter; Fischer, Lars; Althaus, Karina; Knöfler, Ralf; Bakchoul, Tamam
Abstract: Chronic hemorrhagic diathesis in patients showing normal levels of plasmatic clotting factors strongly suggests for congenital platelet disorders. We report on a pediatric patient (male, 3 years, D1) with mild bleeding. A sibling (D2), his mother (D3) and father (D4) were included for laboratory investigation. Platelet counts in D1, D2 and D4 indicated mild thrombocytopenia (100 Gpt/L). D1 and D3 platelets showed significantly diminished aggregation response on arachidonic acid and U46619 stimulation. Immunostaining for platelet proteins on blood smears of D1 and D2 indicated defects in ß1-tubulin. Exon sequencing of TBXA2R and TUBB1 revealed heterozygosity for the novel TBXA2R*c.908T>C (p.L303P) mutation in D1 and D3. TUBB1 was either wild type (D2, D3) or heterozygous (D1, D4) for the common polymorphism TUBB1*c.920G>A (rs6070697; p.R307H). In conclusion, the bleeding phenotype of the index patient can be explained by a diminished platelet function caused by the TBXA2R*c.908T>C mutation inherited from the mother and a mild thrombocytopenia with unknown molecular basis that is inherited from the father.